Intense sub‐micrometre focusing of soft X‐ray free‐electron laser beyond 1016 W cm−2 with an ellipsoidal mirror. (5th August 2019) - Motoyama, Hiroto; Owada, Shigeki; Yamaguchi, Gota; Kume, Takehiro; Egawa, Satoru; Tono, Kensuke; Inubushi, Yuichi; Koyama, Takahisa; Yabashi, Makina; Ohashi, Haruhiko; Mimura, Hidekazu
Abstract : A hybrid focusing system in combination with a Kirkpatrick–Baez mirror system and an ellipsoidal mirror has been developed to produce a sub‐micrometre focus for soft X‐ray free‐electron lasers with an extreme power density beyond 10 16  W cm −2 . Abstract : Intense sub‐micrometre focusing of a soft X‐ray free‐electron laser (FEL) was achieved by using an ellipsoidal mirror with a high numerical aperture. A hybrid focusing system in combination with a Kirkpatrick–Baez mirror was applied for compensation of a small spatial acceptance of the ellipsoidal mirror. With this system, the soft X‐ray FEL pulses were focused down to 480 nm × 680 nm with an extremely high intensity of 8.8×10 16  W cm −2 at a photon energy of 120 eV, which yielded saturable absorption at the L ‐edge of Si (99.8 eV) with a drastic increase of transmittance from 8% to 48%.